2016
DOI: 10.1007/s00259-016-3487-1
|View full text |Cite
|
Sign up to set email alerts
|

18F-FBPA as a tumor-specific probe of L-type amino acid transporter 1 (LAT1): a comparison study with 18F-FDG and 11C-Methionine PET

Abstract: This study shows the utility of F-FBPA as a tumor-specific probe of LAT1 with low accumulation in the inflammatory lesions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
48
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 55 publications
(51 citation statements)
references
References 30 publications
2
48
1
Order By: Relevance
“…A rat glioma C6 cell line, derived from gliomas induced by N -nitrosomethylurea, was provided by the RIKEN BRC (Tsukuba, Japan). Rat xenograft models of C6 glioma were evaluated 3 weeks after the tumor implantation in the subcutaneous region of either side [7]. All animal experiments were performed in compliance with the guidelines of the Institute of Experimental Animal Sciences.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…A rat glioma C6 cell line, derived from gliomas induced by N -nitrosomethylurea, was provided by the RIKEN BRC (Tsukuba, Japan). Rat xenograft models of C6 glioma were evaluated 3 weeks after the tumor implantation in the subcutaneous region of either side [7]. All animal experiments were performed in compliance with the guidelines of the Institute of Experimental Animal Sciences.…”
Section: Methodsmentioning
confidence: 99%
“…18 F-FBPA was prepared as described previously, using an F-1 synthesizer (Sumitomo Heavy Industries, Tokyo, Japan) [7]. PET/CT data were acquired with a small-animal PET system (Inveon PET/CT system, Siemens Medical Solutions) [8].…”
Section: Methodsmentioning
confidence: 99%
“…In our previous studies, we demonstrated high levels of accumulation of various amino acid PET probes, such as 18 F-FBPA, 18 F-FAMT and 11 C-MET, in Oncotarget 1390 www.oncotarget.com C6 glioma. Moreover, we demonstrated the functional expression of LAT1 in these tumors using histology and western blot analyses [5,15]. A western blot analysis of GL261 cells also revealed strong expression of LAT1 [16].…”
Section: Discussionmentioning
confidence: 69%
“…Oncotarget 1389 www.oncotarget.com emission tomography (PET), such as 11 C-methionine ( 11 C-MET), 18 F-fluorodihydroxyphenylalanine ( 18 F-DOPA), and 18 F-fluoroethyltyrosine ( 18 F-FET), are used mainly to evaluate the extent of tumor invasion and differentiate recurrence from radiation necrosis [3,4]. Additionally, phenylalanine (PA) derivatives such as 18 F-fluoro-borono-PA ( 18 F-FBPA) and 4-borono-L-PA (BPA) specifically target tumors and are used mainly in the context of boron neutron capture therapy [5]. They were both reported to be substrates of the L-type amino acid transporter 1 (LAT1) and were found to be taken up selectively by tumors, with minimal physiological accumulation in normal organs [5,6].…”
Section: Research Papermentioning
confidence: 99%
See 1 more Smart Citation